Meminimalkan Sisa Pemotongan Besi Beton dalam Proyek Konstruksi - Bambang Santoso; Sofyan Mufti Prasetiyo; Agung Wijoyo (Jurnal Informatika Universitas Pamulang, 2019)
Construction industries are a must in developing countries. Constructions take part in almost every corner of the country. In construction projects, reinforced concrete plays big part in any construction. A long bar of steel are cut into be several lengths to satisfy the requirements of the buildings to be build. In this process, waste cannot be avoided. And the waste of steel bar is very destructive to environment. This research is to find a way to minimize the waste in the process of cutting steel bars. The algorithm used is Greedy Search. Greedy Search is where the optimized solution in every step is taken, in the hope that the overall solution will be optimized for the problem. Optimized solution here is the minimum waste by the steel bar cutting. This will minimize the cost by the construction companies and at the same time preserve the environment.